How Negative Is the Theology of Dionysius the Areopagite? - Edwards, Mark (Verbum Vitae, 2023)
This paper considers three recent studies on the negative theology of the Neoplatonists and Dionysius the Areopagite. The first is that of Lloyd Gerson, who argues that the One in Plotinus does not lack transcend existence but only definite existence; the second is the contrary thesis of Eric D. Perl that not only the One of Plotinus but the God of Dionysius transcend all being in such a way that they cannot be credited with existence. After some criticism of both the paper turns to the argument of Timothy D. Knepper that even the ineffability of the divine cannot be stated on our present plane of knowledge; it concludes with some reflections on the appeal to present or future experience as alternatives to epistemology as this is commonly understood in the analytical tradition of philosophy.